FROM FACE-SAVING TO SOUL-SEARCHING: ON THE SERVICEABILITY OF OVERAPOLOGIZING IN EDUCATION - Cristian, Alin (Social Science Diliman: A Philippine Journal of Society and Change; Vol 6 No 1 (2010), 2010)
This phenomenological inquiry attempts to render more transparent the connection between students’ failures to deliver as expected in school and their culturally sanctioned, high-frequency style of apologizing for it. In a social environment that overwhelmingly promotes consent, resistance and counteraction may take on increasingly undetectable forms rather than vanish. What could be symptomatic expressions of a deep-level resistance lose their conspicuousness and thus gain in subversive efficacy if trivialized through frequent apologizing. The argument’s conclusion is that by underestimating the educational role of conflict and the person’s capacity to handle certain levels thereof strictly on her own, a culture also deprives its members of the possibility to experience an inner rift apt to break tenacious failure patterns. This disablement remains difficult to legitimize within a global context, although persistently regarded as indispensable to the specific cultural identity education is called to reproduce.
Keywords: overapologizing, symbolic responses, passive resistance, incapacity symptoms, failure patterns, social credit